2012
DOI: 10.1111/j.1744-9987.2012.01147.x
|View full text |Cite
|
Sign up to set email alerts
|

Timing for Initiation of Continuous Renal Replacement Therapy in Patients With Septic Shock and Acute Kidney Injury

Abstract: The optimal timing for renal replacement therapy initiation in septic acute kidney injury (AKI) remains controversial. This study investigates the impact of early versus late initiation of continuous renal replacement therapy (CRRT) on organ dysfunction among patients with septic shock and AKI. Patients were dichotomized into "early" (simplified RIFLE Risk) or "late" (simplified RIFLE Injury or Failure) CRRT initiation. Patients with chronic kidney disease stage 5 or those on long-term dialysis were excluded. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 21 publications
2
20
0
Order By: Relevance
“…Using AKIN stage 3 as a definition for ‘late' start versus AKIN stages 1 and 2 as ‘early start', we did not find an association with mortality or CKD progression. This is consistent with recent studies in critically ill septic AKI patients that found no difference in-hospital mortality when creatinine-based criteria were used to determine ARRT initiation [27,28]. A change in peri-operative serum creatinine levels in critically ill patients may be less reliable as a biomarker of renal injury as it can be influenced by muscle mass, concurrent sepsis, or hemodilution during surgery [29].…”
Section: Discussionsupporting
confidence: 77%
“…Using AKIN stage 3 as a definition for ‘late' start versus AKIN stages 1 and 2 as ‘early start', we did not find an association with mortality or CKD progression. This is consistent with recent studies in critically ill septic AKI patients that found no difference in-hospital mortality when creatinine-based criteria were used to determine ARRT initiation [27,28]. A change in peri-operative serum creatinine levels in critically ill patients may be less reliable as a biomarker of renal injury as it can be influenced by muscle mass, concurrent sepsis, or hemodilution during surgery [29].…”
Section: Discussionsupporting
confidence: 77%
“…Several studies have examined the timing of RRT initiation in AKI patients in the ICU. It is unclear whether the early initiation of RRT improves survival and renal recovery rates [4][5][6][7][8][9]. These studies, however, differ in their definition of early and late initiation.…”
Section: Reviewmentioning
confidence: 99%
“…Several observational studies have assessed the relationships between the timing of RRT and mortality and renal recovery in critically ill patients with AKI requiring RRT [6][7][8]. The largest prospective cohort study, involving patients at 54 ICUs in 23 countries, showed that the timing of RRT influenced outcomes in critically ill patients with severe AKI [7].…”
Section: Reviewmentioning
confidence: 99%
“…and Ostermann et al . In particular, urine output criterion was included in determining AKIN stages, unlike other studies evaluating creatinine‐only or eGFR‐only RIFLE or AKIN criteria …”
Section: Discussionmentioning
confidence: 99%